Description of two new janirid isopods (Isopoda, Asellota, Janiridae) from Korean waters - Kim, Sung Hoon; Kim, Jong Guk; Yoon, Seong Myeong (Zootaxa, 2022)
Two janirid isopods, Caecijaera ciliata sp. nov. and Janiralata truncata sp. nov., are reported from Korean waters in this study. Caecijaera ciliata sp. nov. differs from its congeners by the following features: pereonites 4–7 with large simple setae on the midline of the posterior tergite margins; the pleotelson is angled proximolaterally; the antennula is six-articled; the basis of pereopod Ⅶ is serrated superiorly; and the appendix masculina is not coiled. Janiralata truncata sp. nov. can be distinguished from its related species by the following characteristics: the lateral margin of the cephalothorax has an acute projection anterolaterally; all coxal plates of the pereonites are visible dorsally; male pleopod Ⅰ has a pair of small rounded projections distally near the fusion line of the two first pleopods; the exopod of pleopod Ⅲ has two plumose setae on the distomedial margin.